Cooperative Learning by Jigsaw to Improve Learning Outcomes for Eight-Grade-Students - Imanti Galih Ayu P.P.; Ilaha Mammadova; Edi Sunjayanto Masykuri (Department of English Language Education, Universitas Muhammadiyah Purworejo, Indonesia, 2021)
This Guidance and counseling action research is motivated by the low average value of the student report cards of class VIII SMP Negeri 1 Kesesi, Kabupaten Pekalongan, Indonesia. This study aims to improve the achievement of learning outcomes through the classical service of recognizing learning style using the Jigsaw Cooperative method which was carried out in two cycles, each cycle carried out in two meetings. This research was conducted from August to September 2019, located in class VIII H odd semester of SMP Negeri 1 Kesesi, Kabupaten Pekalongan, Indonesia for the 2019/2020 school year. The type of research is Guidance and Counseling action research with two cycles consisting of two meetings in one cycle, each cycle consisting of planning, implementation, observation, and reflection. Based on the results of the study, the application of the Jigsaw Cooperative learning model in the classical service of Recognize Your Learning Style material can improve learning outcomes for subjects in class VIII H odd semester of SMP Negeri 1 Kesesi, Kabupaten Pekalongan, Indonesia for the 2019/2020 school year. It can be seen from the initial condition to the final condition that there is an increase in average learning outcomes. In the initial conditions, it only showed an average result of 68.67. In the first cycle it rose to 77.75, and in the second cycle it rose to 84.69. This shows an increase from the initial condition to the first cycle of 9.08 points, while from the initial condition to the second cycle there is an increase of 16.02 points. The results showed that the Jigsaw Cooperative learning model could create a fun and effective learning atmosphere so that student learning outcomes increased from the results of the first cycle to the second cycle. In the first cycle the number of students who got a complete score in learning was only 10 students, while there were 23 students who did not complete. In the second cycle, there was an increase in the score, which was 33 students who were complete in learning. It was concluded that the Jigsaw Cooperative method could improve the ability to identify students' learning styles.